Laminar Burning Velocity and Markstein Length of CH4/CO2/Air Premixed Flames at Various Equivalence Ratios and CO2 Concentrations Under Elevated Pressure. Issue 14 (26th October 2021) - Anggono, Willyanto; Hayakawa, Akihiro; Okafor, Ekenechukwu C.; Gotama, Gabriel Jeremy; Wongso, Stevan
ABSTRACT: Biogas is a renewable fuel predominantly composed of carbon dioxide (CO2 ) and methane (CH4 ) in varying proportions. The effects of the varying CO2 proportion need to be clarified for the development of engines. The laminar burning velocity and the burned gas Markstein length of premixed CH4 /CO2 /Air were measured with CO2 concentration ranging from 0.3 to 0.7 dilution ratios. The equivalence ratio was varied from 0.8 to 1.2, the initial pressure was set at 0.5  MPa, and the temperature was set to 298  K . The experiment was performed using a high-pressure constant volume combustion chamber. One-dimensional simulation of the flames was conducted using GRI-Mech 3.0. The results showed a reduction in the laminar burning velocity of CH4 /CO2 /Air mixtures with an increase in CO2 dilution ratio. A non-monotonic relationship was discovered between measured Markstein length and CO2 dilution ratio with different equivalence ratios. It was found that an increase in the CO2 dilution increased the response of the flames to stretch. For the lean and stoichiometric flames, the Markstein length was nearly constant with CO2 dilution of 0–0.5 and decreased with CO2 dilution of 0.7, suggesting an increase in susceptibility of the flame to the intrinsic flame instability. This was found to be mainly due to an increase in the Zel'dovich number and a decrease in the effective Lewis number with CO2 dilution. The Markstein length of the rich flame increased with CO2 dilution as it was more sensitive to CO2 dilution. Thermo-diffusive effects and pure stretch effects had similar influences on the burning velocity of the rich flames with an increase in stretch rate.